Reference gene selection for qRT-PCR analysis in the sweetpotato whitefly, Bemisia tabaci (Hemiptera: Aleyrodidae). - Rumei Li (Public Library of Science (PLoS), 2013)
Background Accurate evaluation of gene expression requires normalization relative to the expression of reliable reference genes. Expression levels of "classical" reference genes can differ, however, across experimental conditions. Although quantitative real-time PCR (qRT-PCR) has been used extensively to decipher gene function in the sweetpotato whitefly Bemisia tabaci, a world-wide pest in many agricultural systems, the stability of its reference genes has rarely been validated. Results In this study, 15 candidate reference genes from B. tabaci were evaluated using two Excel-based algorithms geNorm and Normfinder under a diverse set of biotic and abiotic conditions. At least two reference genes were selected to normalize gene expressions in B. tabaci under experimental conditions. Specifically, for biotic conditions including host plant, acquisition of a plant virus, developmental stage, tissue (body region of the adult), and whitefly biotype, ribosomal protein L29 was the most stable reference gene. In contrast, the expression of elongation factor 1 alpha, peptidylprolyl isomerase A, NADH dehydrogenase, succinate dehydrogenase complex subunit A and heat shock protein 40 were consistently stable across various abiotic conditions including photoperiod, temperature, and insecticide susceptibility. Conclusion Our finding is the first step toward establishing a standardized quantitative real-time PCR procedure following the MIQE (Minimum Information for publication of Quantitative real time PCR Experiments) guideline in an agriculturally important insect pest, and provides a solid foundation for future RNA interference based functional study in B. tabaci.